"With most of it being pictures now, I rarely use it": Understanding Twitter's Evolving Accessibility to Blind Users - Morris, Meredith Ringel; Perkins, Annuska; Yao, Catherine; Bahram, Sina; Bigham, Jeffrey P.; Kane, Shaun K. (Proceedings of CHI 2016, 2016)
Social media is an increasingly important part of modern life. We investigate the use of and usability of Twitter by blind users, via a combination of surveys of blind Twitter users, large-scale analysis of tweets from and Twitter profiles of blind and sighted users, and analysis of tweets containing embedded imagery. While Twitter has traditionally been thought of as the most accessible social media platform for blind users, Twitter’s increasing integration of image content and users’ diverse uses for images have presented emergent accessibility challenges. Our findings illuminate the importance of the ability to use social media for people who are blind, while also highlighting the many challenges such media currently present this user base, including difficulty in creating profiles, in awareness of available features and settings, in controlling revelations of one’s disability status, and in dealing with the increasing pervasiveness of imagebased content. We propose changes that Twitter and other social platforms should make to promote fuller access to users with visual impairments.